Cigarette advertisements: A systemic functional grammar and multimodal analysis - Ananda, Rizki; Fitriani, Siti Sarah; Samad, Iskandar Abdul; Patak, Andi Anto (Universitas Pendidikan Indonesia, 2019)
Drawing on a multimodality theory, this study attempted to investigate the various semiotic resources utilized by a giant Indonesian cigarette company, Sampoerna, and explore how these resources communicate meanings or messages in its billboard advertisements to persuade its potential customers to buy the product. The data were analyzed using Halliday’s systemic functional grammar focusing on ideational meta-function or also known as a representational function in multimodal discourse analysis. The findings revealed that the billboard advertisements were designed to persuade the audience to buy the advertised products implicitly through representational functions attained using narrative and conceptual processes. Whereas the former was realized by employing its typical sub-processes, actional and reactional processes, the latter employed its sub-processes such as classificational, analytical, and symbolic processes. Implicationally, this study has illuminated the possible application of systemic functional grammar within multimodal discourse analysis domain to investigate implicit message(s) conveyed by an advertisement.